The Effect Of Service On Satisfaction Customers At Pt. Meida Tourism Tour And Travel - Syahrul, Syahrul; Andi Mappatompo; Syarthini Indrayani (International Journal of Economic Research and Financial Accounting, 2024)
SYAHRUL. 2024. The Effect of Service on Customer Satisfaction at PT. Meida Wisata Tour And Travel. Thesis, Department of Management, Faculty of Economics and Business, Muhammadiyah University of Makassar. Supervised by Andi Mappatompo and Syarthini Indrayani. The aim of this research is quantitative research with the aim of finding out the effect of service on customer satisfaction at PT. Meida Wisata Tour And Travel. The population and sample used in this research amounted to 165 respondents. The type of data used in this research is quantitative data obtained and related to the problem being studied. Data collection was carried out by observing the distribution of questionnaires and documentation. Based on the results of data research using statistical calculations via Statistical Product and Service Solutions (SPSS) Version 27 software regarding the influence of service on customer satisfaction at PT. Meida Wisata Tour And Travel, the author draws the conclusion that physical evidence (X1), reliability (X2), responsiveness (X3), guarantee (X4), and empathy (X5) have a positive and significant effect on customer satisfaction. This is proven by the physical evidence variable which obtained a t value of 5.902 t table 0.153, variable reliability obtained a t value of 8.452 > t table 0.153, variable responsiveness obtained a t value of 3.573 > t table 0.153, variable assurance obtained a t value of 3.100 > t table 0.153 , and variable empathy obtained a calculated t value of 6.713 > t table 0.153.